Tingkat produktivitas karyawan dilihat dari perspektif lingkungan kerja sosial dan kepuasan kerja - Nazdia, Lusiana Arsyah; Sumiyati, Sumiyati; Widjadjanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2019)
Abstract: The purpose of the research is to find out the influence of social work environment on productivity, the influence of job satisfaction on productivity, and the influence of social work environment and job satisfaction on productivity. The object used as analysis unit on this research is employees of electricity entreprise. The type of study is using verificative with the method is using an explanatory survey of 87 respondents. It was found that the influence of the social work environment to productivity are included in the category are very strong. Job satisfaction is very strong against the influential employee productivity. Social work environment and job satisfaction influence on productivity is very strong. The results also show that social work environment conducive conditions will increase employee productivity. The level of job satisfaction is high, then an electric company employee productivity will increase. In addition, if environmental conditions are conducive to social work and job satisfaction is high, then the employee productivity will increase.